2007
DOI: 10.1002/art.22404
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of therapy and a guarded prognosis in an american cohort of takayasu arteritis patients

Abstract: Objective. To describe the clinical, laboratory, and radiographic manifestations of Takayasu arteritis (TA) in a cohort from the US, evaluate the response to interventions, remission and relapse rates, and disease progression, and compare these observations with those from other cohorts in the US, Japan, India, Italy, and Mexico.Methods. Seventy-five patients were retrospectively studied using a uniform database that included clinical, laboratory, and imaging data. Vascular imaging studies were performed at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
295
3
45

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(359 citation statements)
references
References 46 publications
(38 reference statements)
16
295
3
45
Order By: Relevance
“…Assessing disease activity in TA patients is challenging because clinical, biologic, and radiologic data do not always correlate (1)(2)(3)(4). In the present study, we found a lack of correlation between FDG uptake and biologic or radiologic assessment of disease activity and a trend toward an association between FDG uptake and clinical activity.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Assessing disease activity in TA patients is challenging because clinical, biologic, and radiologic data do not always correlate (1)(2)(3)(4). In the present study, we found a lack of correlation between FDG uptake and biologic or radiologic assessment of disease activity and a trend toward an association between FDG uptake and clinical activity.…”
Section: Discussioncontrasting
confidence: 58%
“…Evaluation of disease activity in patients with TA is challenging because clinical features do not correlate with acute-phase reactants in ϳ50% of cases (1)(2)(3), and imaging modalities do not always correlate with clinical and laboratory parameters (4). The complexity of evaluating disease activity in TA is further underlined by the fact that up to 45% of patients in clinical remission have histologic evidence of active disease (1,5).…”
Section: Conclusion Our Findings Indicate That There Is No Associatimentioning
confidence: 99%
“…1,3) Such patients require retreatment and high cumulative doses of GC, resulting in substantial toxicity and morbidity. Thus, immunosuppressive drugs such as methotrexate (MTX), azathioprine (AZA), cyclosporine A (CsA), cyclophosphamide (CYC), and mycophenolate mofetil (MMF) have been studied with an attempt to control the disease activity and lower doses of GC.…”
mentioning
confidence: 99%
“…10,14,15,18) Severe hypertension, severe functional disability, and evidence of cardiac involvement are good predictors of either death or a major To manage active arteritis, an initial dose of corticosteroid administered at 1 mg/kg/day for one month, and then tapered down to less than 10 mg/day, is the initial mainstay of medical therapy for patients with Takayasu's arteritis. 4,9) However, studies report that only 20% of patients with Takayasu's arteritis maintain remission for 6 months on less than 10 mg prednisone. 4) Since no medical therapies can reverse established vascular stenosis, 4) the combination of medical therapy and subsequent revascularization is crucial in patients with Takayasu's arteritis.…”
Section: Discussionmentioning
confidence: 99%